Physicochemical Properties of PEMA-MgTf2-EMITFSI Polymer Electrolytes - Zain, N.F.; Zainal, N.; Mohamed, N.S. (American Scientific Publishers, 2016)
The present work was carried out to investigate the effects of MgTf2 and EMITFSI ionic liquid on the physicochemical properties of PEMA based electrolytes. Free-standing polymer electrolyte films consisting of poly(ethyl methacrylate), magnesium triflate salt and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ionic liquid were prepared at different weight percentage ratios (wt%) using the solution casting technique. The interactions between the electrolyte constituents were confirmed using Fourier transform infrared spectroscopy. The conductivity of the films was influenced by the content of the doping salt and ionic liquid. The conductivity behavior was then correlated with the results of differential scanning calorimetry. The highest ionic conductivity of 1.72×10-6 S cm-1 at room temperature and 1.97×10-4 S cm-1 at 100 °C was achieved for the sample containing 20 wt% of salt and 30 wt% of ionic liquid. The sample exhibited a wide electrochemical potential stability window between -4.19 to +3.74 V.